Coating slurry for carbon fiber base material and preparation method of coating slurry

By preparing coating slurry with high permeability film forming materials, physique materials, super wetting functional materials and solvents, the problems of low adhesion and poor permeability of carbon fiber substrate coatings are solved, and the effects of high adhesion and simplified process are achieved.

CN119686127APending Publication Date: 2025-03-25SHANGHAI CHINA SHIPBUILDING MATERIALS ENG CO LTD +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411831604.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

The surface of carbon fiber substrate lacks chemically active functional groups, resulting in low adhesion and poor permeability of the coating, requiring cumbersome pretreatment processes and high-temperature curing, affecting the mechanical properties of the material structure.

Method used

The coating slurry consisting of high-permeability film forming materials, physique materials, super wetting functional materials and solvents is used. Through the improvement of formula and process, the coating slurry has excellent permeability and adhesion, and can quickly penetrate the surface gap structure of the carbon fiber substrate to form a strong binding force.

Benefits of technology

It realizes high adhesion and permeability of carbon fiber substrate coating, simplifies the substrate processing process, reduces costs, improves efficiency, and has a wide range of applications, and can be cured at room temperature.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005185683020000061
    Figure BDA0005185683020000061
  • Figure BDA0005185683020000071
    Figure BDA0005185683020000071
Patent Text Reader

Abstract

The invention relates to coating slurry for a carbon fiber base material, which is characterized in that the coating slurry comprises the following raw materials in percentage by weight: 10-30% of high-permeability film-forming material, 15-45% of body material, 5-30% of super-wetting functional material and 5-20% of solvent, and the sum of the raw materials is 100%. When the coating slurry is used, the formula of the coating slurry is simple, the preparation process is simple and convenient, the cost is low, the efficiency is high, and the coating slurry has excellent adhesive force and low base material treatment requirements while having high permeability; the problems that in the prior art, the adhesive force of various coatings to the carbon fiber base material is low, and the construction technology is strict and complex can be solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of coating slurries, in particular to a coating slurry for a carbon fiber substrate and a preparation method thereof, and in particular to a high-permeability and high-adhesion coating slurry for a carbon fiber substrate and a preparation method thereof. Background Art

[0002] Carbon fiber materials have many advantages such as high strength, light weight, and corrosion resistance, so they have attracted more and more attention in the fields of aerospace, medical technology, automobiles, energy, etc. However, due to the smooth surface of carbon fiber materials, the lack of chemically active functional groups, and the chemical inertness of the surface, they seriously affect the adhesion between the substrate and various coatings, thereby reducing the interfacial bonding strength of the carbon fiber substrate and limiting its application in some fields.

[0003] Carbon fiber material is composed of carbon fiber filaments and resin. It is a material with porosity. The air contained in the pores is very likely to cause defects such as pinholes and potholes on the coated surface. When existing coating materials are used for surface coating of carbon fiber materials, due to the chemical inertness of the substrate, the coating has insufficient wettability on the substrate, poor permeability, poor adhesion, and defects such as bubbles and pinholes are prone to appear on the surface. Under normal circumstances, it is necessary to perform rigorous and cumbersome pre-treatment procedures on the carbon fiber, using the impact of high-speed sand flow to clean or sandpaper to roughen the substrate surface, so that the gas inside the carbon fiber matrix can escape, prevent defects such as bubbles in subsequent painting, and obtain a certain degree of cleanliness and different roughness, so that the coating performance on the workpiece surface is improved to a certain extent. At the same time, it is usually necessary to heat and bake the coating to improve the adhesion between the coating and the substrate. But at the same time, the cumbersome pre-treatment process is easy to destroy the mechanical structure of the carbon fiber and affect the structural mechanical properties of the material itself.

[0004] For example: Document CN110328126A discloses a water-based carbon fiber coating and its preparation method and construction process, the water-based carbon fiber coating includes a water-based coating main agent and a water-based curing agent; the main agent includes hydroxyl polyacrylic acid emulsion, leveling agent, wetting agent, dispersant, water and dipropylene glycol methyl ether; the curing agent is water-based polyisocyanate. The construction process is to spray primer, water-based putty, color paint and topcoat on the carbon fiber substrate in sequence, then bake with microwave, then use infrared drying, and then polish, and each layer needs to be baked, dried and polished. The document "Study on the Coating Performance of Epoxy Coating and Carbon Fiber Sheet, Zhao Min, Wang Hao" uses sandpaper to polish carbon fiber sheet and prepare nano-composite coating to improve coating adhesion, and investigates the adhesion mechanism. AFM, SEM and XPS tests show that sandpaper polishing the substrate surface ensures basic roughness, which is conducive to coating spreading. The adhesion of the coating on the board is increased by 25%. The addition of nanoparticles reduces the volume shrinkage of the resin, promotes the formation of polar functional groups, forms chemical bonds with the active groups of carbon fibers, and enhances adhesion.

[0005] However, the existing coatings are still conventional organic compound coatings such as epoxy and acrylic, which still do not fundamentally change the problem of adhesion to the carbon fiber substrate, and still require strict and cumbersome pre-treatment processes and high heating and curing conditions. In order to fundamentally solve the problem of carbon fiber substrate coating, it is urgent to develop a coating slurry with good permeability to carbon fiber materials, excellent adhesion, and room temperature curing, so that it can fully penetrate into the gaps of the substrate, simplify the carbon fiber material substrate processing process and coating process, and improve the coating adhesion and coating quality. Summary of the invention

[0006] The purpose of the present invention is to provide an improved coating slurry for a carbon fiber substrate and a preparation method thereof. Through the improvement of the formula and process, the coating slurry has excellent permeability and adhesion, can quickly penetrate the surface gap structure of the carbon fiber substrate, and form a strong bonding force with the substrate.

[0007] In order to achieve the above-mentioned purpose, the technical solution of the present invention is: a coating slurry for a carbon fiber substrate, characterized in that the coating slurry is composed of raw materials in the following weight percentages: 10% to 30% of high permeability film-forming material, 15% to 45% of body material, 5% to 30% of super wetting functional material and 5% to 20% of solvent, and the total of the above raw materials is 100%.

[0008] Preferably, the high permeability film-forming material is a film-forming material in which the acidic silane group is completely hydrolyzed; the body material is one or a combination of ultrafine ceramic powder, ultrafine zinc oxide powder, ultrafine glass powder, and organic siloxane.

[0009] Furthermore, the super wetting functional material is at least one of the following materials: hyperbranched acrylic copolymer, hyperbranched acrylic graft polymer; the solvent is one or a combination of the following materials: distilled water, deionized water, municipal tap water.

[0010] A method for preparing a coating slurry for a carbon fiber substrate, characterized in that the preparation method comprises the following steps: a. slowly adding weighed high-permeability film-forming materials, physical materials, and super-wetting functional materials into a solvent, and stirring to make the above materials evenly dispersed; b. putting the mixed slurry into a grinder for fine grinding, with the grinding fineness being less than or equal to 30 microns; c. filtering the obtained high-permeability slurry.

[0011] Preferably, in step a, the body material is one or a combination of ultrafine ceramic powder, ultrafine zinc oxide powder, ultrafine glass powder, and organic siloxane; the superwetting functional material is at least one of the following materials: hyperbranched acrylic copolymer, hyperbranched acrylic graft polymer. In step a, the high permeability film-forming material is a film-forming material in which the acidic silane group is completely hydrolyzed; the solvent is one or a combination of the following materials: distilled water, deionized water, and municipal tap water.

[0012] Preferably, the following raw materials are weighed in weight percentage: 35% of high permeability film-forming material, 40% of body material, 15% of superwetting functional material and 10% of solvent; wherein the body material is a mixture of ultrafine ceramic powder, ultrafine zinc oxide powder and organic siloxane in a mass ratio of 1:1:1; the superwetting functional material is a mixture of hyperbranched acrylic copolymer and hyperbranched acrylic graft polymer in a mass ratio of 1:1.

[0013] Preferably, the following raw materials are weighed in weight percentage: 30% high permeability film-forming material, 40% body material, 20% superwetting functional material, and 10% solvent; wherein the body material is a mixture of ultrafine ceramic powder and ultrafine zinc oxide powder in a mass ratio of 3:1; and the superwetting functional material is a hyperbranched acrylic polymer.

[0014] Preferably, the following raw materials are weighed in weight percentage: 20% high permeability film-forming material, 40% body material, 30% superwetting functional material, and 10% solvent; wherein the body material is a mixture of ultrafine glass powder and ultrafine zinc oxide powder in a mass ratio of 1:1; and the superwetting functional material is a hyperbranched acrylic polymer.

[0015] Compared with the prior art, the technical solution of the present invention not only improves the overall technical solution, but also includes many improvements in details. Specifically, it has the following beneficial effects:

[0016] 1. The improved solution of the present invention is that the coating slurry is composed of the following raw materials in weight percentage: 10% to 30% of high permeability film-forming material, 15% to 45% of body material, 5% to 30% of super wetting functional material and 5% to 20% of solvent, and the sum of the above raw materials is 100%. The coating slurry of this formula has excellent permeability and adhesion, can quickly penetrate the surface gap structure of the carbon fiber substrate, and form a strong bonding force with the substrate. At the same time, the coating slurry of this formula has relatively low requirements for the early treatment of the carbon fiber substrate, simplifies the construction process, reduces costs, and improves efficiency;

[0017] 2. In the preparation method of the technical solution of the present invention, the weighed high permeability film-forming material, the body material, and the super-wetting functional material are slowly added to the solvent, and stirred to make the above materials dispersed evenly; then the mixed slurry is put into a grinder for fine grinding; finally, the high permeability slurry obtained after filtration has a simple process flow, is easy to realize industrialization, has low cost, and high production efficiency;

[0018] 3. The coating slurry prepared by the present invention has a wide range of applications, can be cured at room temperature, and has a simple use process. The slurry is mixed and diluted with a solvent in proportion and sprayed on the surface of a carbon fiber substrate. It has a wide range of applications and is easy to promote and utilize. DETAILED DESCRIPTION

[0019] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0020] The present invention provides a coating slurry for a carbon fiber substrate, which is different from the prior art in that the coating slurry is composed of raw materials in the following weight percentages: 10% to 30% of a high-permeability film-forming material, 15% to 45% of a body material, 5% to 30% of a super-wetting functional material and 5% to 20% of a solvent, and the total of the above raw materials is 100%.

[0021] A method for preparing a coating slurry for a carbon fiber substrate, characterized in that the preparation method comprises the following steps: a. slowly adding weighed high-permeability film-forming material, physical material, and super-wetting functional material into a solvent, and stirring to make the above materials evenly dispersed; b. putting the mixed slurry into a grinder for fine grinding; c. filtering the obtained high-permeability slurry.

[0022] When in use, the coating slurry of the present invention not only has a simple formula and a simple preparation process, but also has low cost and high efficiency. The coating slurry of the present invention has high permeability while having excellent adhesion and low substrate processing requirements, and can solve the problems of low adhesion of various coatings to carbon fiber substrates and harsh and complex construction processes in the prior art.

[0023] Example 1

[0024] This embodiment describes a high-permeability and high-adhesion coating slurry for a carbon fiber substrate, which is made of the following raw materials by mass: 30% of a high-permeability film-forming material, 40% of a body material, 20% of a superwetting functional material, and 10% of a solvent; wherein the high-permeability film-forming material is an acidic silane-based complete hydrolyzate ( SIVO 140); the body material is a mixture of ultrafine ceramic powder and ultrafine zinc oxide powder in a mass ratio of 3:1; the superwetting functional material is a hyperbranched acrylic polymer ( WE 3323); the solvent was distilled water.

[0025] The preparation process includes the following steps: slowly adding high permeability film-forming materials, body materials, and super-wetting functional materials into the solvent, stirring to make them dispersed evenly; then putting the mixed slurry into a grinder for fine grinding; filtering to obtain the high permeability coating slurry. This slurry has high permeability, excellent adhesion and low substrate processing requirements, so as to solve the problems of low adhesion of various coatings to carbon fiber substrates and strict and complex construction processes in the prior art.

[0026] Example 2

[0027] In this embodiment, a high permeability and high adhesion coating slurry for a carbon fiber substrate is made of the following raw materials by mass: 20% of a high permeability film-forming material, 40% of a body material, 30% of a superwetting functional material, and 10% of a solvent; wherein the acidic silane-based complete hydrolyzate ( SIVO 140); the body material is a mixture of ultrafine glass powder and ultrafine zinc oxide powder in a mass ratio of 1:1; the superwetting functional material is a hyperbranched acrylic polymer ( WE3323); the solvent is deionized water.

[0028] The preparation method comprises the following steps: a. slowly adding the weighed high permeability film-forming material, physical material, and super-wetting functional material into the solvent, and stirring to make the above materials dispersed evenly; b. putting the mixed slurry into a grinder for fine grinding, and the grinding fineness is less than or equal to 30 microns; c. filtering to obtain the high permeability coating slurry. This coating slurry has excellent permeability and adhesion, can quickly penetrate the surface gap structure of the carbon fiber substrate, and form a strong bonding force with the substrate; the slurry preparation process is simple and easy to realize industrial production.

[0029] Example 3

[0030] In this embodiment, the following raw materials are weighed in weight percentage: 35% of high permeability film-forming material, 40% of body material, 15% of superwetting functional material and 10% of solvent; wherein the high permeability film-forming material is acidic silane-based complete hydrolyzate ( SIVO 140); the body material is a mixture of ultrafine ceramic powder, ultrafine zinc oxide powder and organic siloxane in a mass ratio of 1:1:1; the superwetting functional material is a hyperbranched acrylic polymer ( WE 3323) and hyperbranched acrylic acid graft polymer (WE 3220) are mixed in a mass ratio of 1:1; the solvent is municipal tap water.

[0031] The preparation method comprises the following steps: a. slowly adding the weighed high permeability film-forming material, physical material, and super-wetting functional material into the solvent, and stirring to make the above materials dispersed evenly; b. putting the mixed slurry into a grinder for fine grinding, and the grinding fineness is not greater than 30 microns; c. filtering to obtain the high permeability coating slurry. This coating slurry has excellent permeability and adhesion, can quickly penetrate the surface gap structure of the carbon fiber substrate, and form a strong bonding force with the substrate; the slurry preparation process is simple and easy to realize industrial production; the slurry has a wide range of applicability and can be cured at room temperature; the slurry has low requirements for the pre-treatment of the carbon fiber substrate, and simplifies the construction process.

[0032] Example 4

[0033] In this embodiment, the following raw materials are weighed in weight percentage: 40% of high permeability film-forming material, 40% of body material, 10% of superwetting functional material, and 10% of solvent; wherein the high permeability film-forming material is acidic silane-based complete hydrolyzate ( SIVO 140); the body material is a mixture of ultrafine zinc oxide powder and organic siloxane in a mass ratio of 1:1; the superwetting functional material is a hyperbranched acrylic acid graft polymer (WE3220) produced by BASF; and the solvent is municipal tap water.

[0034] The preparation method comprises the following steps: a. slowly adding the weighed high permeability film-forming material, physical material, and super-wetting functional material into the solvent, and stirring to make the above materials dispersed evenly; b. putting the mixed slurry into a grinder for fine grinding, and the grinding fineness is not greater than 30 microns; c. filtering to obtain the high permeability coating slurry. This coating slurry has excellent permeability and adhesion, can quickly penetrate the surface gap structure of the carbon fiber substrate, and form a strong bonding force with the substrate; the slurry preparation process is simple and easy to realize industrial production; the slurry has a wide range of applicability and can be cured at room temperature; the slurry has low requirements for the pre-treatment of the carbon fiber substrate, and simplifies the construction process.

[0035] Then three comparative examples were prepared, as shown in Table 1, wherein comparative example 1: the coating slurry was made of the following raw materials in mass fraction: 70% of the body material, 20% of the superwetting functional material, and 10% of the solvent; wherein the body material was made of ultrafine ceramic powder and ultrafine zinc oxide powder mixed in a mass ratio of 3:1; the superwetting functional material was a hyperbranched acrylic polymer ( WE 3323); the solvent was distilled water.

[0036] Comparative Example 2: The coating slurry is made of the following raw materials in mass fraction: 5% high permeability film-forming material, 55% body material, 20% super wetting functional material, and 10% solvent; wherein the high permeability film-forming material is an acidic silane-based complete hydrolyzate ( SIVO 140); the body material is a mixture of ultrafine ceramic powder and ultrafine zinc oxide powder in a mass ratio of 3:1; the superwetting functional material is a hyperbranched acrylic polymer ( WE 3323); the solvent was distilled water.

[0037] Comparative Example 3: The coating slurry is made of the following raw materials in mass fraction: 30% waterborne epoxy resin, 40% body material, 20% superwetting functional material, and 10% solvent; wherein the body material is a mixture of ultrafine ceramic powder and ultrafine zinc oxide powder in a mass ratio of 3:1; the superwetting functional material is a hyperbranched acrylic polymer ( WE 3323); the solvent was distilled water.

[0038] Table 1 Raw material composition of Examples 1 to 4 and Comparative Examples 1 to 3, %

[0039]

[0040] The slurries prepared in Examples 1 to 4 and Comparative Examples 1 to 3 were mixed with deionized water as a solvent, and applied to the carbon fiber substrate by spraying, and cured at room temperature to form a film. The paint film was then tested, and the coating adhesion was tested according to the method specified in GB / T5210, with the adhesion required to be ≥4MPa; the coating water resistance was tested according to the method specified in GB / T 5209; and the coating appearance was tested according to the method specified in GB 1792. The test results are shown in Table 2:

[0041] Table 2 Test results of coating properties of Examples 1 to 4 and Comparative Examples 1 to 3

[0042]

[0043] It can be seen from Table 2 that the high-permeability and high-adhesion slurry for the carbon fiber substrate of the present invention has a significant effect on improving the adhesion of the substrate, thereby achieving high adhesion performance of the carbon fiber substrate coating and simplifying the substrate processing process, which is the advantage of the present invention.

[0044] The above content is a further detailed description of the present invention in combination with specific preferred embodiments, and it cannot be determined that the specific implementation of the present invention is limited to the above descriptions. For ordinary technicians in the technical field to which the present invention belongs, several simple deductions or substitutions can be made without departing from the concept of the present invention, which should be regarded as falling within the scope of protection of the present invention.

Claims

1. A coating slurry for a carbon fiber substrate, characterized in that: The coating slurry is composed of raw materials in the following weight percentages: 10% to 30% of high permeability film-forming material, 15% to 45% of body material, 5% to 30% of super wetting functional material and 5% to 20% of solvent, the total of the above raw materials is 100%.

2. The coating slurry for carbon fiber substrate according to claim 1, characterized in that: High permeability film-forming material: a film-forming material in which acidic silane groups are completely hydrolyzed; the body material is one or a combination of ultrafine ceramic powder, ultrafine zinc oxide powder, ultrafine glass powder, and organic siloxane.

3. The coating slurry for carbon fiber substrate according to claim 1, characterized in that: The super wetting functional material is at least one of the following materials: hyperbranched acrylic acid copolymer, hyperbranched acrylic acid graft polymer; the solvent is one or a combination of the following materials: distilled water, deionized water, municipal tap water.

4. The method for preparing a coating slurry for a carbon fiber substrate according to claim 1, characterized in that: The preparation method comprises the following steps: a. slowly adding weighed high permeability film-forming material, body material and super wetting functional material into a solvent, and stirring to make the above materials dispersed evenly; b. Put the mixed slurry into a grinder for fine grinding, with the grinding fineness being less than or equal to 30 microns; c. Filter to obtain the high permeability slurry.

5. The method for preparing a coating slurry for a carbon fiber substrate according to claim 1, characterized in that: In step a, the base material is one or a combination of ultrafine ceramic powder, ultrafine zinc oxide powder, ultrafine glass powder, and organic siloxane; the superwetting functional material is at least one of the following materials: hyperbranched acrylic copolymer, hyperbranched acrylic graft polymer.

6. The method for preparing a coating slurry for a carbon fiber substrate according to claim 1, characterized in that: In step a, the high permeability film-forming material is a film-forming material in which the acidic silane group is completely hydrolyzed; the solvent is one or a combination of the following materials: distilled water, deionized water, municipal tap water.

7. The method for preparing a coating slurry for a carbon fiber substrate according to claim 5, characterized in that: The following raw materials are weighed in weight percentage: 35% of high permeability film-forming material, 40% of bulk material, 15% of superwetting functional material and 10% of solvent; wherein the bulk material is a mixture of ultrafine ceramic powder, ultrafine zinc oxide powder and organic siloxane in a mass ratio of 1:1:1; the superwetting functional material is a mixture of hyperbranched acrylic copolymer and hyperbranched acrylic graft polymer in a mass ratio of 1:

1.

8. The method for preparing a coating slurry for a carbon fiber substrate according to claim 5, characterized in that: Weigh the following raw materials in percentage by weight: 30% of high permeability film-forming material, 40% of bulk material, 20% of superwetting functional material, and 10% of solvent; wherein the bulk material is a mixture of ultrafine ceramic powder and ultrafine zinc oxide powder in a mass ratio of 3:1; and the superwetting functional material is a hyperbranched acrylic polymer.

9. The method for preparing a coating slurry for a carbon fiber substrate according to claim 5, characterized in that: Weigh the following raw materials in percentage by weight: 20% of high permeability film-forming material, 40% of bulk material, 30% of superwetting functional material, and 10% of solvent; wherein the bulk material is a mixture of superfine glass powder and superfine zinc oxide powder in a mass ratio of 1:1; and the superwetting functional material is a hyperbranched acrylic polymer.

Citation Information

Patent Citations

  • Waterborne carbon fiber coating and preparation method and construction technology thereof

    CN110328126A